Nutritive value of sugarcane bagasse ammoniated with four urea doses - Carvalho, Gleidson Giordano Pinto de; Pires, Aureliano José Vieira; Veloso, Cristina Mattos; Magalhães, Alberti Ferreira; Freire, Mario Alberto Lopes; Silva, Fabiano Ferreira da; Silva, Robério Rodrigues; Carvalho, Bruna Mara Aparecida de (Pesquisa Agropecuaria Brasileira, 2006)
The objective this experiment was to evaluate chemical-bromatologic composition and in vitro dry matter digestibility of sugarcane bagasse submitted to ammonization with urea. The treatments were four urea dose added to the sugarcane bagasse and addition of 1.2% (DM basis) of soybean as urease source. The experimental design utilized was a completely randomized. The bagasse was stored in PVC silos with 5.3 L capacity, which were opened after 110 days of ammonization. With the urea dose addition to the bagasse, crude protein levels increased linearly. The neutral detergent fiber, acid detergent fiber, hemicelluloses, cellulose, lignin and total carbohydrates levels decreased, while the acid detergent insoluble nitrogen, neutral detergent insoluble nitrogen, nonfibrous carbohydrates, ammonia nitrogen levels and pH increased significantly with urea addition. At evaluated dose, the urea added to bagasse provides increase in nitrogen compounds content, decrease of fiber compounds, and increases the in vitro dry matter digestibility. Estimated by regression equation, the addition of 2.62% urea to sugarcane bagasse provides the minimum crude protein level to good functioning of the rumen.